Method for producing porous silicon material, porous silicon material and power storage device
The production of a porous silicon material with Al and Ti, utilizing acid treatment to remove Al, addresses the issue of silicon expansion, enhancing the charge-discharge characteristics and cycle stability in power storage devices.
Patent Information
- Application Number
- JP2021179650
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-11-02
AI Technical Summary
Existing methods for manufacturing porous silicon materials fail to adequately suppress defects caused by the expansion and contraction of silicon during charging and discharging, leading to deterioration of charge and discharge characteristics.
A method involving the production of a silicon alloy containing Al and Ti, followed by rapid cooling and solidification, and subsequent removal of the Al component using acids or alkalis to create a porous silicon material with a three-dimensional network structure, small pore sizes, and high porosity, reinforced by SiTi and AlSiTi compounds.
The method results in a porous silicon material that significantly reduces volume expansion and contraction, improving the cycle characteristics of power storage devices by maintaining high capacity and energy density, as demonstrated in lithium-ion secondary batteries.
Smart Images

Figure 0007601745000003 
Figure 0007601745000004 
Figure 0007601745000005
Abstract
Description
[Technical field]
[0001] Disclosed herein are methods for producing porous silicon materials, porous silicon materials and power storage devices. [Background technology]
[0002] Conventionally, in a silicon negative electrode material, a porous silicon has been proposed in which 70 parts by mass of lump Si and 30 parts by mass of Al powder are mixed, and then the mixture is granulated by gas atomization using a molten alloy and helium gas under an argon atmosphere, and then Al is removed with hydrochloric acid (see, for example, Patent Document 1). It is said that this porous silicon can completely suppress pulverization due to expansion and contraction of the active material volume during charging and discharging, peeling of the active material from the current collector, and lack of contact with the conductive material. In addition, as a method for producing a silicon material, a method has been proposed in which an intermediate alloy element containing Mg, Co, Cr, Cu, Fe, etc. and a Si alloy of Si are separated into a second phase in which the intermediate alloy element and the molten metal element are replaced in a molten metal containing a predetermined molten metal element, and Si fine particles, and the second phase is removed to obtain a porous silicon material (see, for example, Patent Document 2). It is said that this porous silicon material can have high capacity and high cycle characteristics. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-214054 A [Patent Document 2] JP 2012-82125 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the manufacturing method of the above-mentioned Patent Document 1, an alloy containing Si and Al is used to make the material porous, but the method is still insufficient in suppressing defects due to the expansion and contraction of Si. In the manufacturing method of the porous silicon material of Patent Document 2, a silicon alloy containing an intermediate alloy element is melted and replaced with a molten metal containing a predetermined molten metal element, that is, a high-temperature treatment is required, and a simple manufacturing process is desired.
[0005] The present disclosure has been made in consideration of such problems, and has as its main object to provide a method for producing a porous silicon material, a porous silicon material, and an electricity storage device that can further suppress the deterioration of charge-discharge characteristics. [Means for solving the problem]
[0006] As a result of intensive research to achieve the above-mentioned object, the inventors have discovered that by producing a silicon alloy containing Al and Ti and removing the compound containing Al, a porous silicon material can be obtained that can further suppress the deterioration of charge-discharge characteristics, and have completed the manufacturing method for the porous silicon material, the porous silicon material, and the electricity storage device disclosed herein.
[0007] That is, the method for producing the porous silicon material of the present disclosure includes: a precursor process for obtaining a silicon alloy precursor by melting and rapidly solidifying a raw material containing Ti in a range of 5 at% to 15 at% and Al in a range of 10 at% to 50 at% and the remainder being Si, where Si, Ti and Al are taken as the total of 100 at%; a porosity forming step of removing an Al component contained in the silicon alloy to obtain a porous silicon material; It includes.
[0008] The porous silicon material of the present disclosure comprises: The pore size distribution range determined by mercury intrusion porosimetry is in the range of 1 nm to 250 nm, the material contains skeletal silicon with a three-dimensional mesh structure having voids, contains SiTi compounds and / or AlSiTi compounds, and has an average porosity in the range of 10 vol. % to 50 vol. %.
[0009] The electricity storage device of the present disclosure comprises: a positive electrode including a positive electrode active material; A negative electrode containing the above-mentioned porous silicon material as a negative electrode active material; an ion conductive medium interposed between the positive electrode and the negative electrode and conducting lithium ions; It is equipped with the following: Effect of the Invention
[0010] This disclosure can further suppress the deterioration of charge / discharge characteristics in materials containing Si. The reason for this effect is presumed to be as follows. For example, the theoretical capacity of a silicon negative electrode for a lithium-ion secondary battery is 4199 mAh / g, which is about 10 times the theoretical capacity of ordinary graphite, 372 mAh / g, and further increases in capacity and energy density are expected. On the other hand, silicon that has absorbed lithium ions has a high charge / discharge characteristic of Li 4.4 Si, and the volume expands to about four times that of silicon before lithium absorption. In the present disclosure, elements or compounds other than silicon, silicon titanium, and aluminum silicon titanium compounds are selectively dissolved to produce porous silicon with small pore size and large porosity. By simply removing elements or compounds other than silicon, silicon titanium, and aluminum silicon titanium compounds, porous silicon can be easily provided in the atmosphere without the need for large-scale equipment. In addition, the obtained porous silicon material has a cage-like silicon skeleton reinforced with silicon titanium compounds and aluminum silicon titanium compounds, and has an average pore diameter of 250 nm or less. When such a porous silicon material with a small pore size, large porosity, and reinforced skeleton is used in an electricity storage device such as a lithium ion battery, the volume expansion and contraction is alleviated, and the cycle characteristics are improved, making it easy to obtain a high-performance electricity storage device. [Brief description of the drawings]
[0011] [Figure 1] Al-Si-Ti phase diagram at 10at%Ti. [Diagram 2] Al-Si-Ti phase diagram at 60at%Si. [Diagram 3] FIG. 2 is an explanatory diagram showing an example of the structure of an electricity storage device 10. [Figure 4] 1 is a SEM image of the surface of the porous silicon of Experimental Example 3. [Diagram 5] 1 is a cross-sectional SEM image of porous silicon in Experimental Example 3. [Figure 6] 1 shows XRD measurement results after acid treatment in Experimental Example 1. [Figure 7] 4 shows XRD measurement results after acid treatment in Experimental Example 2. [Figure 8] 4 shows XRD measurement results after acid treatment in Experimental Example 3. [Figure 9] 3 is a pore distribution curve of the porous silicon material of Experimental Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Method of manufacturing porous silicon material) The manufacturing method of the porous silicon material of the present disclosure includes a precursor process and a porosity process. In the precursor process, a raw material containing Si, Al, and Ti is melted and rapidly solidified to obtain a precursor of a silicon alloy. In the porosity process, the Al component contained in the silicon alloy is removed to obtain a porous silicon material. First, the raw material composition will be described.
[0013] FIG. 1 is an Al-Si-Ti phase diagram at 10 at% Ti. FIG. 2 is an Al-Si-Ti phase diagram at 60 at% Si. In general, when a melt of a eutectic composition with a minimum liquidus line in the equilibrium diagram of a eutectic AB alloy is solidified, a eutectic structure is formed in which the A phase and the B phase are phase-separated into fibers (lamellae). At this time, the size of the lamellar structure formed becomes finer as the cooling rate increases, and a nano-sized structure is formed at a cooling rate of 1000°C / s or more. If only the A element can be selectively removed from this eutectic structure by acid treatment, a material consisting of the B element characterized by a eutectic structure can be obtained. The microstructure changes by adjusting the composition of the A element and the B element near the eutectic composition, and a porous body having a structure in which the crystallized phase consisting of the B element is connected is obtained. Considering Al as the A element in the alloy and Si and Ti as the B elements, the equilibrium diagram shows that near the Al-Si-Ti ternary eutectic composition, SiTi compounds, AlSiTi compounds, and Si crystallize, while primary Al and AlTi compounds crystallize or precipitate. The solidification structure forms a lamellar structure consisting of SiTi compounds, AlSiTi compounds, AlTi compounds, eutectic Si, primary Si, and primary Al. Compounds that dissolve in acid include primary Al and AlTi compounds, so it is presumed that the structure after acid treatment will be a skeletal porous body consisting of the remaining SiTi compounds, AlSiTi compounds, eutectic Si, and primary Si.
[0014] (Precursor process) In the precursor process, it is preferable to use a raw material containing Ti in the range of 5 at% to 15 at% and Al in the range of 10 at% to 50 at% and the remainder being Si, when the total of Si, Ti and Al is 100 at%. The raw material may contain unavoidable impurities. The unavoidable impurities are components that inevitably remain during the purification of any of Si, Ti and Al, and examples thereof include Fe, C, Cu, Ni and P. It is preferable that the amount of unavoidable impurities is as small as possible, and for example, when the total of Si, Ti and Al is 100 at%, it is preferably 5 at% or less, and more preferably 2 at% or less. The compounding ratio of Ti is, for example, preferably 6 at% or more, and may be 7.5 at% or more. The compounding ratio of Ti is preferably 14 at% or less, and may be 12.5 at% or less. The compounding ratio of Al is preferably 50 at% or less, more preferably less than 50 at%, further preferably 40 at% or less, and may be 30 at% or less. The compounding ratio of Al is preferably 10 at% or more, more preferably 15 at% or more, and may be 20 at% or more. A silicon alloy containing Al or Ti in such a range is preferable because it can increase the porosity and obtain voids of a more suitable shape and size. If the Al content is high, when the alloy is melted to form an alloy and then rapidly cooled, a single phase of Al precipitates in a large area, and many voids can be formed. The cooling rate is preferably as rapid as possible, for example, 10 at% or more from the molten state. 2 ℃ / s or more 10 8 ° C. / s or less.
[0015] In this step, when the raw material is melted, high-frequency crucible melting in an inert gas atmosphere such as Ar is preferable, but any melting method may be used. In the precursor step, the alloy obtained from the raw material may be granulated. In this granulation process, the molten metal of the raw material of the silicon alloy may be cast into a mold, and the obtained ingot may be crushed and granulated. In addition, the method of granulating the silicon alloy may be one or more of the molten metal of the silicon alloy, the gas atomization method, the water atomization method, and the roll quenching method. In the gas atomization method and the water atomization method, an alloy powder is obtained. On the other hand, in the roll quenching method, a thin strip alloy is obtained, so that it may be crushed and powdered after that. Since the powder obtained by the roll quenching method has a fine alloy structure, porous silicon having fine pores can be obtained after the elution process. Among these, the gas atomization method is more preferable as the method of granulating the silicon alloy. In the gas atomization, it is preferable to perform the molten metal in an Ar atmosphere, and it is preferable to perform the granulation in an Ar or He atmosphere.
[0016] In the precursor process, the silicon alloy is preferably granulated to have an average particle size in the range of 0.1 μm to 100 μm. For example, the average particle size of the particles is preferably 0.5 μm to 10 μm, more preferably 1 μm to 5 μm, and even more preferably 1 μm to 3 μm. The silicon alloy particles may be appropriately selected according to the characteristics required for the power storage device. Here, the average particle size of the particles is determined by observing the particles with a scanning electron microscope (SEM), counting the major axis of each particle as the diameter of the particle, and dividing the average value by the number of particles. The particles obtained by this granulation process will be the average particle size of the aggregate of porous particles to be finally obtained.
[0017] In this precursor process, a raw material containing Al, Ti, and Si as well as a second element containing one or more of Ca, Cu, Mg, Na, Sr, and P may be used. Among these, the second element is preferably one or more of Ca, Na, and Sr. The content of the second element is preferably less than that of Al and Ti, and is preferably in the range of 10 mass% or less, more preferably 5 mass% or less, based on the entire silicon alloy.
[0018] (Porous process) In the porosity forming step, a treatment is performed to remove substances other than Si from the silicon alloy particles produced above. Examples of substances other than Si include Al and its compounds, and Ti and its compounds. In this step, it is preferable to selectively remove the Al component, that is, the Al phase and its compounds, using an acid or alkali. The acid or alkali used is preferably one that dissolves elements and / or compounds other than silicon in the silicon alloy and does not dissolve silicon, and examples of such acids include hydrochloric acid, sulfuric acid, and sodium hydroxide. This acid or alkali is preferably an aqueous solution. The concentration of the acid or alkali is not particularly limited as long as it is within a range that can remove Al and its compounds, and Ti and its compounds, and can be, for example, in the range of 1 mol / L to 5 mol / L. This removal treatment may be performed by heating at, for example, 30°C to 60°C. In addition, it is preferable to perform the removal treatment by immersing the silicon alloy particles in an acid or alkali solution and stirring for about 1 to 5 hours. The obtained porous silicon material is then washed and dried.
[0019] In the porosity forming step, substances other than Si may be removed in the range of 85% by mass to 100% by mass. For example, Al, Ti, other oxygen, etc. may remain, but when used as an electrode active material, it is preferable that they are less in terms of charge / discharge capacity. In addition, components such as Al and Ti are preferably contained in a predetermined amount or more in terms of reinforcing the silicon skeleton and improving durability. In this step, a porous silicon material containing a SiTi compound and / or an AlSiTi compound may be obtained. Examples of SiTi compounds include Si x Ti y(x, y are arbitrary numbers), and Si 3 Ti 5 Or Si 4 Ti 5 Examples of the AlSiTi compound include Al a S b Ti c Compounds (where a, b, and c are any numbers) may be used, and Ti 33 Al 15 S 52 (τ 2 The SiTi compound and the AlSiTi compound may be poorly soluble in acid or alkali.
[0020] In the porosity forming step, it is preferable to obtain a porous silicon material containing SiTi compounds in a range of 10 mass% or less when the total of the Si, SiTi compounds and AlSiTi compounds is taken as 100 mass%. In addition, in the porous silicon material, it is preferable to contain SiTi compounds in an amount of 0.5 mass% or more, and it may be contained in an amount of 1 mass% or more. In addition, in the porous silicon material, it is preferable to contain SiTi compounds in an amount of 7.5 mass% or less, and it may be contained in an amount of 5 mass% or less. In addition, in this step, it is preferable to obtain a porous silicon material containing AlSiTi compounds in a range of 50 mass% or less when the total of the Si, SiTi compounds and AlSiTi compounds is taken as 100 mass%. In addition, in the porous silicon material, it is preferable to contain AlSiTi compounds in an amount of 1 mass% or more, and it may be contained in an amount of 5 mass% or more. In addition, in the porous silicon material, it is preferable to contain AlSiTi compounds in an amount of 40 mass% or less, and it may be contained in an amount of 30 mass% or less. In this step, Si 3 Ti 5 and Ti 33 Al 15 S 52 It is preferable to obtain a porous silicon material in which
[0021] In the porosification step, a porous silicon material having an average porosity in the range of 10 volume % or more and 50 volume % or less may be obtained. This average porosity is a value measured by a mercury porosimeter. This average porosity is preferably 15 volume % or more, and may be 20 volume % or more, for example. The average porosity is preferably less than 50 volume %, more preferably 49 volume % or less, and may be 40 volume % or less or 30 volume % or less, for example. A larger average porosity is more responsive to volume changes during occlusion of carrier ions, and a smaller average porosity is preferable because the amount of Si present per unit volume increases.
[0022] (Porous silicon material) The porous silicon material of the present disclosure may be one produced by the above-mentioned manufacturing method. Here, the detailed description of each physical property of the porous silicon material is omitted since it is the same as that of the above-mentioned manufacturing method. The porous silicon material has a pore size distribution range of 1 nm to 500 nm as determined by mercury intrusion porosimetry. The pore size may be 10 nm or more, 50 nm or more, or 100 nm or more. The pore size is preferably 250 nm or less, may be 200 nm or less, or may be 150 nm or less. In the porous silicon material, the average pore size as determined by mercury intrusion porosimetry may be in the range of 5 nm to 500 nm, or may be in the range of 10 nm to 250 nm.
[0023] The porous silicon material includes skeletal silicon having a three-dimensional network structure with voids, and includes a SiTi compound and / or an AlSiTi compound. It is presumed that the SiTi compound and the AlSiTi compound are responsible for reinforcing the silicon skeleton. The porous silicon material preferably contains the SiTi compound in the range of 10 mass% or less. The porous silicon material preferably contains the AlSiTi compound in the range of 50 mass% or less. The SiTi compound and the AlSiTi compound are preferably more in terms of supplementing the skeleton reinforcement, and are preferably less in terms of the charge / discharge capacity of the electricity storage device.
[0024] The porous silicon material has an average porosity in the range of 10 volume % or more and 50 volume % or less. This average porosity is preferably 40 volume % or less, more preferably 35 volume % or less, and may be 30 volume % or less. In addition, the average porosity is preferably 15 volume % or more, more preferably 20 volume % or more, and may be 25 volume % or more. From the viewpoint of the volume change of the material, this average porosity is preferably larger, and from the viewpoint of the charge / discharge capacity of the electricity storage device, this average porosity is preferably smaller. This average porosity is a value measured by a mercury porosimeter.
[0025] The porous silicon material preferably has an average particle size of 0.1 μm or more, more preferably 1 μm or more, and may be 5 μm or more. The particles preferably have an average particle size of 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. The porous silicon material preferably contains 70 at% or more of Si when the total of Si, Al, and Ti is 100 at%, excluding oxygen and unavoidable impurities. The Si content is more preferably 75 at% or more, more preferably 80 at% or more, and may be 85 at% or more. The Si content is preferably higher from the viewpoint of charge / discharge capacity, and may be lower from the viewpoint of relative skeletal reinforcement. The Al content is preferably in the range of 0.5 at% to 15 at%, more preferably 12.5 at% or less, more preferably 10 at% or less, and may be 7.5 at% or less. The Al content is more preferably 1 at% or more, more preferably 2 at% or more, and may be 2.5 at% or more. The content of Ti is preferably in the range of 0.5 at% or more and 25 at% or less. The content of Ti is more preferably 20 at% or less, further preferably 17.5 at% or less, and may be 17 at% or less. The content of Ti is more preferably 1 at% or more, more preferably 5 at% or more, further preferably 10 at% or more, and may be 12% or more. The content of Al or Ti is preferably higher from the viewpoint of supplementing the reinforcement of the skeleton, and is preferably lower from the viewpoint of the charge / discharge capacity of the power storage device, since it is a component that does not charge / discharge. Furthermore, the porous silicon material may contain one or more of Ca, Cu, Mg, Na, Sr, and P as a second element in the range of 15 mass% or less. Furthermore, the porous silicon material may contain inevitable impurities in addition to Si, Al, and Ti. It is preferable that the second element and inevitable impurities are less.
[0026] (Electrodes for electricity storage devices) The electrode for a power storage device comprises the porous silicon material described above as an electrode active material. This electrode is either a positive electrode or a negative electrode based on the potential of the counter electrode relative to the potential of the electrode active material, but when lithium is used as a carrier, it is preferable to use the electrode as a negative electrode. This electrode can be used, for example, in a lithium ion secondary battery, a hybrid capacitor, an air battery, etc. The electrode for a power storage device may be one in which the average porosity of the porous silicon material is compressed to a range of 5 volume % or more and 50 volume % or less. In this electrode, the porosity of the porous silicon material may be reduced by compressing it during production. For example, when porous silicon particles are used as a negative electrode active material for a lithium ion secondary battery, the smaller the pores are, the more uniform the alloying of lithium ions is, so that stress concentration is reduced and deterioration of the electrode itself can be prevented. The average porosity of the porous silicon material after compression may be appropriately adjusted according to the characteristics required for the electrode for a power storage device, and may be, for example, 5 volume % or more or 10 volume % or more. The average porosity of the compressed porous silicon material may be, for example, 30% by volume or less, or 20% by volume or less.
[0027] The electrode for the power storage device may be one in which the porous silicon material is formed on a current collector and fixed on the current collector. This electrode can be produced by a process in which the porous silicon material is mixed with a conductive material and a binder in a solvent as necessary to form a paste and then coated on the current collector, or a process in which the porous silicon material is mixed with a conductive material and a binder as necessary and then pressed onto the current collector. In this electrode, the content of the porous silicon material is preferably higher, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more. The conductive material is not particularly limited as long as it is an electron conductive material that does not adversely affect the battery performance, and for example, a mixture of one or more of graphite such as natural graphite (scale graphite, scale graphite) and artificial graphite, acetylene black, carbon black, ketjen black, carbon whisker, needle coke, carbon fiber, and metal (copper, nickel, aluminum, silver, gold, etc.) can be used. The binder plays a role of binding the active material particles and the conductive material particles, and may be, for example, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, or thermoplastic resins such as polypropylene and polyethylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM rubber, natural butyl rubber (NBR), or the like, either alone or as a mixture of two or more kinds. In addition, a cellulose-based aqueous binder or an aqueous dispersion of styrene butadiene rubber (SBR) may also be used. As the solvent, for example, an organic solvent such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethylenetriamine, N,N-dimethylaminopropylamine, ethylene oxide, or tetrahydrofuran may be used. In addition, a dispersant, a thickener, or the like may be added to water, and the active material may be slurried with latex such as SBR. Examples of the application method include roller coating such as an applicator roll, screen coating, doctor blade method, spin coating, bar coater, and the like, and any of these can be used to obtain any thickness and shape.The current collector may be appropriately selected depending on the potential of the active material, and may be, for example, aluminum, titanium, stainless steel, nickel, iron, copper, baked carbon, conductive polymer, conductive glass, or aluminum or copper whose surface is treated with carbon, nickel, titanium, silver, or the like for the purpose of improving adhesion, conductivity, and oxidation resistance. The surfaces of these may also be subjected to oxidation treatment. The shape of the current collector may be a foil, film, sheet, net, punched or expanded, lath, porous, foamed, or fiber group. The thickness of the current collector may be, for example, 1 to 500 μm. The amount of the active material complex formed may be appropriately set depending on the desired performance required for the power storage device.
[0028] In this electrode, the electrode active material may contain, in addition to the porous silicon material, an active material other than the porous silicon material, so long as both a low confining pressure and a capacity retention rate can be achieved. For example, the electrode active material may contain a carbonaceous material or Li 4 Ti 5 O 12 However, from the viewpoint of further increasing the battery capacity, it is preferable that the porous silicon material accounts for, for example, 50 mass % or more, and preferably 90 mass % or more, of the entire electrode active material taken as 100 mass %.
[0029] (Electricity storage device) The electricity storage device of the present disclosure includes an electrode having the porous silicon material described above. The electricity storage device may include a positive electrode, a negative electrode, and an ion-conducting medium interposed between the positive electrode and the negative electrode and conducting carrier ions. The porous silicon material can be used as the negative electrode active material. The electricity storage device may be any one of a lithium ion secondary battery, a hybrid capacitor, and an air battery. In the positive electrode, a sulfide containing a transition metal element, an oxide containing lithium and a transition metal element, or the like can be used as the positive electrode active material. Specifically, TiS 2 , TiS 3 , MoS 3 , FeS 2Transition metal sulfides such as, with a basic composition formula of Li (1-x) MnO 2 (where 0 < x < 1, and the same applies hereinafter) or Li (1-x) Mn 2 O 4 Lithium manganese composite oxides such as, with a basic composition formula of Li (1-x) CoO 2 Lithium cobalt composite oxides such as, with a basic composition formula of Li (1-x) NiO 2 Lithium nickel composite oxides such as, with a basic composition formula of Li (1-x) Ni a Co b Mn c O 2 (where a + b + c = 1) Lithium nickel cobalt manganese composite oxides such as, with a basic composition formula of LiV 2 O 3 Lithium vanadium composite oxides such as, with a basic composition formula of V 2 O 5 Transition metal oxides such as can be used. Among these, lithium transition metal composite oxides, for example, LiCoO 2 , LiNiO 2 , LiMnO 2 , Li (1-x) Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc. are preferred. Note that the "basic composition formula" means that other elements such as Al and Mg may be included. Alternatively, the positive electrode active material may be a carbonaceous material used in capacitors or lithium-ion capacitors. Examples of the carbonaceous material include activated carbons, cokes, vitreous carbons, graphites, non-graphitizable carbons, pyrolytic carbons, carbon fibers, carbon nanotubes, polyacenes, etc. Among these, activated carbons showing a high specific surface area are preferred. The activated carbon as the carbonaceous material preferably has a specific surface area of 1000 m 2 / g or more, and more preferably 1500 m 2 / g or more. When the specific surface area is 1000 m 2 / g or more, the discharge capacity can be further increased. The specific surface area of this activated carbon is preferably 3000 m from the ease of production.2 / g or less, and 2 The conductive material, binder, solvent, current collector, and the like used in the positive electrode can be appropriately selected from those exemplified for the electrode described above.
[0030] The ion-conducting medium may be a non-aqueous electrolyte solution containing a supporting salt, a non-aqueous gel electrolyte solution, etc. Examples of the solvent for the non-aqueous electrolyte solution include carbonates, esters, ethers, nitriles, furans, sulfolanes, and dioxolanes, which may be used alone or in combination. Specific examples of carbonates include cyclic carbonates such as ethylene carbonate, propylene carbonate, vinylene carbonate, butylene carbonate, and chloroethylene carbonate; chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl-n-butyl carbonate, methyl-t-butyl carbonate, di-i-propyl carbonate, and t-butyl-i-propyl carbonate; cyclic esters such as γ-butyl lactone and γ-valerolactone; chain esters such as methyl formate, methyl acetate, ethyl acetate, and methyl butyrate; ethers such as dimethoxyethane, ethoxymethoxyethane, and diethoxyethane; nitriles such as acetonitrile and benzonitrile; furans such as tetrahydrofuran and methyltetrahydrofuran; sulfolanes such as sulfolane and tetramethylsulfolane; and dioxolanes such as 1,3-dioxolane and methyldioxolane. Among these, a combination of cyclic carbonates and chain carbonates is preferred. This combination not only provides excellent cycle characteristics, which represent the battery characteristics during repeated charging and discharging, but also allows for a well-balanced viscosity of the electrolyte, the electric capacity of the resulting battery, and the battery output. The supporting salt is, for example, LiPF 6 , LiBF 4 , LiAsF 6 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF3 SO 2 ) 3 , LiSbF 6 , LiSiF 6 , LiAlF 4 , LiSCN, LiClO 4 , LiCl, LiF, LiBr, LiI, LiAlCl 4 Among these, LiPF 6 , LiBF 4 , LiAsF 6 , LiClO 4 and inorganic salts such as LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 From the viewpoint of electrical properties, it is preferable to use one or more salts selected from the group consisting of organic salts such as those mentioned above in combination. The concentration of this supporting salt in the non-aqueous electrolyte is preferably 0.1 mol / L or more and 5 mol / L or less, and more preferably 0.5 mol / L or more and 2 mol / L or less. When the concentration of the supporting salt is 0.1 mol / L or more, a sufficient current density can be obtained, and when it is 5 mol / L or less, the electrolyte can be more stabilized. In addition, a phosphorus-based, halogen-based, or other flame retardant may be added to this non-aqueous electrolyte.
[0031] Also, instead of the liquid ion-conducting medium, a solid ion-conducting polymer can be used as the ion-conducting medium. As the ion-conducting polymer, for example, a polymer gel composed of a polymer such as acrylonitrile, ethylene oxide, propylene oxide, methyl methacrylate, vinyl acetate, vinylpyrrolidone, vinylidene fluoride, and a supporting salt can be used. Furthermore, an ion-conducting polymer can be used in combination with a non-aqueous electrolyte. As the ion-conducting medium, in addition to the ion-conducting polymer, an inorganic solid electrolyte, a mixed material of an organic polymer electrolyte and an inorganic solid electrolyte, or an inorganic solid powder bound by an organic binder can be used.
[0032] The power storage device may have a separator between the negative electrode and the positive electrode. The separator is not particularly limited as long as it has a composition that can withstand the range of use of the lithium secondary battery, and examples thereof include polymer nonwoven fabrics such as polypropylene nonwoven fabrics and polyphenylene sulfide nonwoven fabrics, and thin microporous films of olefin resins such as polyethylene and polypropylene. These may be used alone or in combination.
[0033] The shape of the electricity storage device is not particularly limited, but examples thereof include coin type, button type, sheet type, laminated type, cylindrical type, flat type, and square type. The electricity storage device may also be applied to large devices used in electric vehicles and the like. FIG. 3 is an explanatory diagram showing an example of the structure of an electricity storage device 10. The electricity storage device 10 has a positive electrode 12, a negative electrode 15, and an ion conductive medium 18. The positive electrode 12 has a positive electrode active material 13 and a current collector 14. The negative electrode 15 has a negative electrode active material 16 and a current collector 17. The negative electrode active material 16 is the porous silicon material 21 described above, and has voids 23.
[0034] (All-solid-state lithium-ion secondary battery) The power storage device is preferably an all-solid-state lithium ion secondary battery. In the case of an all-solid-state battery, the change in performance due to the electrolyte can be further suppressed, and safety can be further improved, which is preferable. The all-solid-state lithium ion secondary battery may include a positive electrode containing a positive electrode active material, a negative electrode which is the above-mentioned electrode for the power storage device, and a solid electrolyte which is interposed between the positive electrode and the negative electrode and conducts lithium ions. The positive electrode may be any of those shown in the above-mentioned power storage device. The negative electrode may be the above-mentioned electrode for the power storage device.
[0035] The solid electrolyte may be, for example, a garnet-type oxide containing at least Li, La, and Zr. 7.0+x-y (La 3-x ,A x )(Zr 2-y ,T y )O 12It may also be such. However, A is one or more of Sr and Ca, T is one or more of Nb and Ta, and it satisfies 0 < x ≤ 1.0 and 0 < y < 0.75. Alternatively, the solid electrolyte has a basic composition (Li 7-3z+x-y M z )(La 3-x A x )(Zr 2-y T y )O 12 or may be a garnet-type oxide represented by (Li 7-3z+x-y M z )(La 3-x A x )(Y 2-y T y )O 12 However, in the formula, element M is one or more of Al and Ga, element A is one or more of Ca and Sr, T is one or more of Nb and Ta, and it may be such that 0 ≤ z ≤ 0.2, 0 ≤ x ≤ 0.2, and 0 ≤ y ≤ 2. In this basic composition formula, it is more preferable to satisfy 0.05 ≤ z ≤ 0.1. In this basic composition formula, it is more preferable to satisfy 0.05 ≤ x ≤ 0.1. Also, in this basic composition formula, it is more preferable to satisfy 0.1 ≤ y ≤ 0.8. Within such a range, the ionic conductivity can be made more suitable.
[0036] Alternatively, as the solid electrolyte, for example, common Li 3 N, Li 14 Zn(GeO 4 ) 4 called LISICON, sulfide Li 3.25 Ge 0.25 P 0.75 S 4 , perovskite-type La 0.5 Li 0.5 TiO 3 , (La 2 / 3 Li 3x □ 1 / 3-2x )TiO 3 (□: atomic vacancy), garnet-type Li 7 La 3 Zr 2 O 12 , LiTi 2 (PO4 ) 3 , Li 1.3 M 0.3 Ti 1.7 (PO 3 ) 4 (M=Sc, Al) and the like. Also, glass ceramics 80Li 2 S·20P 2 S 5 Li obtained from glass with the composition (mol%) 7 P 3 S 11 Furthermore, Li, a sulfide-based material with high electrical conductivity, 10 Ge 2 P.S. 2 Glass-based inorganic solid electrolytes include Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li 4 SiO 4 , Li 2 SP 2 S 5 , Li 3 PO 4 -Li 4 SiO 4 , Li 3 BO 4 -Li 4 SiO 4 , and SiO 2 , GeO 2 , B 2 O 3 , P 2 O 5 Li as a glass-based material 2 O is used as a network modifier. 2 S-GeS 2 system, Li 2 S-GeS 2 -ZnS, Li 2 S-Ga 2 S 2 system, Li 2S-GeS 2 -Ga 2 S 3 system, Li 2 S-GeS 2 -P 2 S 5 system, Li 2 S-GeS 2 -SbS 5 system, Li 2 S-GeS 2 -Al 2 S 3 system, Li 2 S-SiS 2 system, Li 2 SP 2 S 5 system, Li 2 S-Al 2 S 3 system, LiS-SiS 2 -Al 2 S 3 system, Li 2 S-SiS 2 -P 2 S 5 These solid electrolytes may be formed into a plate shape and disposed between the positive electrode and the negative electrode.
[0037] The all-solid-state lithium-ion secondary battery may further include a restraining member that restrains a stack of a positive electrode, a solid electrolyte, and a negative electrode in a stacking direction. The restraining member may include, for example, a pair of plate-shaped parts that sandwich the stack from both ends in the stacking direction of the stack, a rod-shaped part that connects the pair of plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the gap between the pair of plate-shaped parts by a screw structure or the like.
[0038] As described above in detail, the present disclosure can further suppress the deterioration of charge / discharge characteristics in materials containing Si. The reason for this effect is presumed to be as follows. For example, a silicon negative electrode for a lithium-ion secondary battery has a theoretical capacity of 4199 mAh / g, which is about 10 times the theoretical capacity of general graphite, 372 mAh / g, and further increases in capacity and energy density are expected. On the other hand, silicon that has absorbed lithium ions has a high capacity of Li 4.4Si, and the volume expands to about four times that of silicon before lithium absorption. According to the present disclosure, the Al component substances other than silicon contained in the silicon alloy are selectively removed by using an acid or alkali that dissolves them, and a porous silicon material with a small pore size and a large porosity can be easily produced. In addition, a compound containing Ti is contained as a microstructure, and this compound strengthens the silicon skeleton, so that the capacity deterioration caused by the skeleton fluctuation due to repeated charging and discharging can be further suppressed. When such a porous silicon material with a small pore size and a large porosity is used in an electricity storage device such as a lithium ion secondary battery, the volume expansion and contraction are greatly alleviated, and therefore, for example, the charge and discharge characteristics such as the charge and discharge cycle characteristics are improved, and therefore a high-performance electricity storage device can be easily obtained.
[0039] It goes without saying that the present disclosure is in no way limited to the above-described embodiment, and can be embodied in various forms as long as it falls within the technical scope of the present disclosure. EXAMPLES
[0040] Specific examples of the porous silicon and electricity storage device according to the present disclosure that have been produced will be described below as experimental examples. Experimental Examples 1 to 3 are working examples of the present disclosure, and Experimental Example 4 is a comparative example.
[0041] [Preparation of porous silicon materials] (Experimental Example 1) 45.5% by mass of 10 mm square block Al, 37.7% by mass of block Si and 16.8% by mass of sponge-like Ti were weighed and mixed, and melted by high-frequency heating in an Ar inert atmosphere to obtain a molten alloy. This molten alloy was subjected to gas atomization using Ar inert gas to obtain AlSiTi alloy powder with an average particle size of 3 μm (precursor process). The quenching rate was 10 6 The AlSiTi alloy powder contains Si, τ 2 (Ti 33 Al 15 S 52 ), (Al,Si) 3 Ti, Si 3 Ti5 The AlSiTi alloy powder has an atomic composition of Al-40at%Si-10at%Ti. X-ray diffraction analysis of the powder obtained after acid treatment revealed Si, (Al,Si) 3 The presence of Ti and Al phases and Si phases was confirmed. Next, the obtained alloy powder was placed in 3 mol / L hydrochloric acid diluted in pure water, stirred at room temperature of 25°C for 1 hour, and then filtered while being thoroughly washed, and dried in a vacuum drying oven at 30°C for 2 hours (porosity forming process). In this way, the porous silicon material of Experimental Example 1 was produced.
[0042] (Experimental Example 2) A porous silicon material of Experimental Example 2 was produced in the same manner as in Experimental Example 1 above, except that 47.2 mass% Al, 19 mass% Si, and 16.6 mass% sponge Ti were used. The atomic composition is Al-50at%Si-10at%Ti. An acid treatment was carried out under the same conditions as in Experimental Example 1 to produce the porous silicon material of Experimental Example 2.
[0043] (Experimental Example 3) A porous silicon material of Experimental Example 3 was produced in the same manner as in Experimental Example 1 above, except that 56 mass% Al, 56.2 mass% Si, and 16.7 mass% sponge Ti were used. The atomic composition is Al-60at%Si-10at%Ti. An acid treatment was carried out under the same conditions as in Experimental Example 1 to produce the porous silicon material of Experimental Example 3.
[0044] (Experimental Example 4) The silicon material in Experimental Example 4 was a Si powder having an average particle size of 5 μm.
[0045] (Physical property measurement of porous silicon materials) The acid-treated porous silicon powder was dissolved in HF and HNO 3The samples were dissolved in water and subjected to elemental analysis using ICP optical emission spectroscopy (ICP-OES, Hitachi High-Tech Science PS3520UVDDII II). In addition, observation and elemental analysis were performed using a scanning electron microscope (SEM, HITACHI S-4300) and energy dispersive X-ray analysis (EDAX, HITACHI S-4300). In addition, the pore distribution was measured using a mercury porosimeter (Quantachrome POWERMASTER60GT).
[0046] (Results and Discussion) Fig. 4 is a surface SEM image of the porous silicon of Experimental Example 3, and Fig. 5 is a cross-sectional SEM image of the porous silicon of Experimental Example 3. As shown in Fig. 4, it was confirmed that Al components such as primary crystal Al were dissolved from the Si alloy by the acid treatment to form porous silicon particles. Furthermore, as shown in Fig. 5, when the cross section of the particle was observed, a structure in which SiTi compounds and AlSiTi compounds were precipitated on skeletal silicon of a three-dimensional network structure of Si was confirmed. It was found that voids were formed by dissolving primary crystal Al and Al compounds in the silicon compound with acid, and porous silicon particles were obtained.
[0047] FIG. 6 shows the results of XRD measurement after the acid treatment in Experimental Example 1. FIG. 7 shows the results of XRD measurement after the acid treatment in Experimental Example 2. FIG. 8 shows the results of XRD measurement after the acid treatment in Experimental Example 3. After the acid treatment, in Experimental Examples 1 and 2, Si, τ 2 (Ti 33 Al 15 S 52 ) was detected, and in Experimental Example 3, Si, τ 2 (Ti 33 Al 15 S 52 ), Si 3 Ti 5 The Al phase and (Al,Si) phase were probably formed by acid treatment. 3 It was presumed that Ti was dissolved and these areas became pores.
[0048] FIG. 9 is a pore distribution curve of the porous silicon material of Experimental Example 3 measured by a mercury porosimeter. Since the mercury porosimeter detects voids between particles, the voids between particles were obtained from the atomized powder before the acid treatment, and the pore diameter and pore volume of the pores were obtained. The pore size obtained from the SEM images shown in FIG. 4 and FIG. 5 was calculated to be several nm to about 200 nm. The pore distribution of the porous silicon material obtained from the mercury porosimeter was in the range of 5 to 200 nm, which was equivalent to the range obtained from the SEM. The pore size obtained from the mercury porosimeter in Experimental Example 3 was most common in the vicinity of 80 nm, the average pore size was 61 nm, and the porosity was 29 vol.%. In Experimental Examples 1 and 2, the average pore size was 85 nm and 76 nm, and the porosity was 47 vol.% and 37 vol.%, respectively. As the Al blending composition decreased, the porosity and average pore size tended to decrease.
[0049] Elemental composition (at%) of the raw materials in Experimental Examples 1 to 4, elemental composition (at%) after acid treatment, compound composition ratio (Si, τ 2 (Ti 33 Al 15 S 52 ), Si 3 Ti 5 The phase (mol%), porosity (volume%) by mercury intrusion porosimetry, and average pore size (nm) are summarized in Table 1. After acid treatment, Al and AlTi compounds were dissolved, and Si was the main component, and τ 2 and / or Si 3 Ti 5 In Experimental Examples 1 to 3, the compound composition was 60 to 87 mol of Si, 3 Ti 5 is 0 to 4 mol, τ 2 (Ti 33 Al 15 S 52 ) was in the range of 9 to 40 mol. Moreover, the porosity of Experimental Examples 1 to 3 was 29 to 47 vol. %, and the average pore diameter was 61 nm to 85 nm, which showed high porosity.
[0050] [Table 1]
[0051] (Preparation of lithium secondary batteries using non-aqueous electrolyte) Each of the silicon materials of Experimental Examples 1 to 4 was used as the negative electrode active material, and 60% by mass of this, 20% by mass of acetylene black with an average particle size of 2 μm as a conductive material, and 20% by mass of polyimide as a binder were weighed and mixed, and N-methylpyrrolidone was added and stirred to prepare a negative electrode composite slurry. Next, this slurry was applied to a copper foil with a thickness of 20 μm, dried, and rolled to prepare a negative electrode with a thickness of 50 μm. The prepared negative electrode was punched out into a circle with a diameter of 16 mm, and a porous polyethylene separator was sandwiched between this negative electrode and metallic lithium was layered as a counter electrode to form a laminate. Next, LiPF was added to a mixed solvent of fluoroethylene carbonate (FEC) / ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) in a volume ratio of 1.5:3:4:3, and LiPF 6 An electrolyte solution containing 1 mol / L of 1-pyridine-2-phosphate ether was added to the laminate to produce a lithium secondary battery, which is a Tom cell type small battery cell. The resulting lithium secondary battery was repeatedly charged and discharged for 10 cycles at a current density of 0.2 C in a battery voltage range of 0.005 V to 1.5 V.
[0052] (Characteristics of lithium secondary batteries using non-aqueous electrolytes) The initial discharge capacity (mAh / g), the discharge capacity after 10 cycles (mAh / g), and the capacity retention rate (%) of Experimental Examples 1 to 4 are shown in Table 2. The capacity retention rate is the discharge capacity Q 1 and the discharge capacity Q at the 10th cycle 10 Using and, Q 10 / Q 1 ×100. In Experimental Examples 1 to 3, the silicide phase and τ 2Since the Al phase was present and the Si phase was relatively small, the initial discharge capacity tended to be smaller than that of Experimental Example 4. Moreover, in Experimental Examples 1 to 3, the discharge capacity tended to increase with the decrease in the Al amount. On the other hand, in Experimental Example 4, the capacity retention rate decreased to 28% after 10 cycles. This was presumed to be because silicon particles without voids could not absorb the volume change, and a defect occurred in the electrode. On the other hand, in the lithium secondary batteries of Experimental Examples 1 to 3, the capacity retention rate was an extremely good value of 98% or more, and it was found that the electrode was stable. It was found that, as in Experimental Examples 1 to 3, when a compound phase containing Ti is further included in a porous silicon material showing a porosity in the range of 10 to 50 volume %, the deterioration of cycle characteristics can be further suppressed by reinforcing the Si skeleton, and the capacity retention rate can be increased.
[0053] [Table 2]
[0054] It goes without saying that the present invention is in no way limited to the above-mentioned experimental examples, and can be embodied in various forms so long as they fall within the technical scope of the present invention. [Industrial Applicability]
[0055] The present disclosure is applicable to the technical field of secondary batteries. [Explanation of symbols]
[0056] 10 electricity storage device, 12 positive electrode, 13 positive electrode active material, 14 current collector, 15 negative electrode, 16 negative electrode active material, 17 current collector, 18 ion conductive medium, 21 porous silicon material, 23 void.
Claims
1. a precursor process for obtaining a precursor of a silicon alloy by melting and rapidly solidifying a raw material containing Ti in a range of 5 at % to 15 at % and Al in a range of 10 at % to 50 at % and the remainder being Si, where the total of Si, Ti and Al is 100 at %; a porosity forming step of removing an Al component contained in the silicon alloy to obtain a porous silicon material; A method for producing a porous silicon material comprising:
2. The method for producing a porous silicon material according to claim 1 , wherein in the porosity forming step, an Al component is selectively removed with an acid or an alkali.
3. The method for producing a porous silicon material according to claim 1 or 2, wherein the porous silicon material obtained in the porosity forming step contains a SiTi compound and / or an AlSiTi compound.
4. 4. The method for producing a porous silicon material according to claim 1, wherein in the porosity forming step, the porous silicon material obtained has an average porosity in the range of 10 volume % or more and 50 volume % or less.
5. The method for producing a porous silicon material according to any one of claims 1 to 4, wherein in the precursor step, the molten silicon alloy is granulated to have an average particle size in the range of 0.1 μm to 100 μm by any one of a gas atomization method, a water atomization method, and a roll quenching method.
6. the pore size distribution range determined by mercury intrusion porosimetry is in the range of 1 nm to 500 nm, the pore size distribution ranges from ... Porous silicon material.
7. The SiTi compound is Si 3 Ti 5 The AlSiTi compound is preferably Ti, 33 A 15 S 52 The porous silicon material according to claim 6, wherein the content is in the range of 50 mass % or less.
8. 8. The porous silicon material according to claim 6 or 7, having an average porosity of 40 vol.% or less.
9. a positive electrode including a positive electrode active material; A negative electrode comprising the porous silicon material according to any one of claims 6 to 8 as a negative electrode active material; an ion conductive medium interposed between the positive electrode and the negative electrode and conducting lithium ions; A power storage device comprising:
Citation Information
Patent Citations
Negative electrode active material for lithium secondary battery, its manufacturing method, and lithium secondary battery
JP2004214054A
Porous silicon particle and method for manufacturing the same
JP2012082125A
Negative electrode active substance material and power storage device
JP2020145053A
Porous silicon, electrode, power storage device, and method for manufacturing porous silicon
JP2021014380A
Manufacturing method of porous silicon grain, manufacturing method of electrode for electricity storage device, manufacturing method of whole solid lithium ion secondary battery, porous silicon grain, electrode for electricity storage device, and whole solid lithium ion secondary battery
JP2021123517A
